Revisited Nonlinear and Non-Ideal Vibrations - Balthazar, J. M. [UNESP]; Felix, J. L. P.; Segla, S.; Tuma, J.; Petrikova, I; Pesek, L.; Zapomel, J.; Kruisova, A.; Gendelman, O.; Berezovski, A. (Technical University Liberec, 2011)
In this paper, an overview on non-ideal vibrations (NIS) is presented, concerning the mitigation of vibration of two (NIS) inverted pendulums. We detected the presence of nonlinear interactions and an energy transfer in the system, due to the effects of both cubic nonlinearity and suspension damping.
Keywords: Inverted pendulums; energy transfer; Sommerfeld effect